2011
DOI: 10.1073/pnas.1119203109
|View full text |Cite
|
Sign up to set email alerts
|

Activation of growth hormone releasing hormone (GHRH) receptor stimulates cardiac reverse remodeling after myocardial infarction (MI)

Abstract: Both cardiac myocytes and cardiac stem cells (CSCs) express the receptor of growth hormone releasing hormone (GHRH), activation of which improves injury responses after myocardial infarction (MI). Here we show that a GHRH-agonist (GHRH-A; JI-38) reverses ventricular remodeling and enhances functional recovery in the setting of chronic MI. This response is mediated entirely by activation of GHRH receptor (GHRHR), as demonstrated by the use of a highly selective GHRH antagonist (MIA-602). One month after MI, ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 35 publications
13
82
0
Order By: Relevance
“…Following the seminal description by Beltrami et al (16) of clusters of cKit cells in the postnatal mammalian heart, several laboratories, including ours, suggested that cKit marks CPs (16)(17)(18)(19), a finding that led to the clinical testing of these cells for heart repair (20). Recently, a straightforward genetic fate-mapping study showed that a relatively small proportion of murine myocardium is derived from cKit + CPs, leading to the conclusion that the cardiomyogenic capacity of cKit + CPs is functionally insignificant (21).…”
Section: Creert2mentioning
confidence: 81%
“…Following the seminal description by Beltrami et al (16) of clusters of cKit cells in the postnatal mammalian heart, several laboratories, including ours, suggested that cKit marks CPs (16)(17)(18)(19), a finding that led to the clinical testing of these cells for heart repair (20). Recently, a straightforward genetic fate-mapping study showed that a relatively small proportion of murine myocardium is derived from cKit + CPs, leading to the conclusion that the cardiomyogenic capacity of cKit + CPs is functionally insignificant (21).…”
Section: Creert2mentioning
confidence: 81%
“…Our group recently demonstrated that JI-38, a synthetic agonist of the growth hormone-releasing hormone receptor (GHRH-R), has cardioprotective effects and also stimulates cardiac reverse remodeling in a rodent model of myocardial infarction (22,35,36). These findings were associated with an increase in the number of CSCs in vivo.…”
mentioning
confidence: 99%
“…The anesthesia agent was the mixture of ketamine (100 mg/kg) and xylazine (10 mg/kg). The pre-treatment period and dosage of MZ-5-156 and JI-38 were optimized by previous studies [15,16]. Serum and plasma samples were obtained from whole blood by centrifugation at 3,000 rpm for 15 min.…”
Section: Animals and Treatmentsmentioning
confidence: 99%